PEMBERIAN KAYU MANIS TERHADAP NYERI LUKA JAHITAN PADA IBU NIFAS DI PUSKESMAS PADASUKA - Antri Ariani; Hani Oktafiani; Milenia Anugrah (NHM PRESS, 2022)
Suture wound pain is a normal condition that occurs in postpartum women who are sutured. There are several methods that can reduce wound pain, suture wound pain, namely with pharmacological drugs and herbal medicines, one of which is cinnamon. Cinnamon contains eugenol compounds which are analgesic so that they can reduce stitch wound pain. The purpose of this study was to determine the effect of giving cinnamon decoction on the pain of perineal sutures in postpartum mothers at the Padasuka Public Health Center in Bandung. This research method uses a descriptive method with a continuity of care approach through a case study. The subjects used in this study were postpartum mothers for the intervention of giving cinnamon decoction. The research instrument used a questionnaire sheet and an NRS (Numeric Rating Scale) observation sheet. The sample of this research is 3 respondents. Some of the therapeutic effects of cinnamon can be seen in the administration of cinnamon decoction from the third and fourth days. The active compounds contained in cinnamon include cinnamaldehyde, eugenol, cinnzeylanine, cinzeylanol, arabinoxylan, 2-hydroxycinnamaldehyde, and 2-benzoloxycinnamaldehyde (Shen et al. al, 2012). The intervention of giving cinnamon decoction showed that cinnamon could also be used as an analgesic and as a cause of injury.